2021
DOI: 10.1063/5.0058561
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic study of alcohol-based deep eutectic solvents

Abstract: The applicability of deep eutectic solvents is determined by their physicochemical properties. In turn, the properties of eutectic mixtures are the result of the components’ molar ratio and chemical composition. Owing to the relatively low viscosities displayed by alcohol-based deep eutectic solvents (DESs), their application in industry is more appealing. Modeling the composition–property relationships established in polyalcohol-based mixtures is crucial for both understanding and predicting their behavior. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Most of the works on the structures of classical DESs are based on ChCl, such as reline [ 64 , 70 , 76 , 123 , 208 , 209 , 210 , 211 , 212 ] (HBD is urea), ethaline [ 161 , 210 , 213 , 214 ] (HBD is ethylene glycol), glyceline [ 82 , 210 , 215 ] (HBD is glycerol), and propoline [ 216 , 217 ] (HBD is propylene glycol). Over the last five years, their structures and properties have been investigated intensively and the main interactions have been determined.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the works on the structures of classical DESs are based on ChCl, such as reline [ 64 , 70 , 76 , 123 , 208 , 209 , 210 , 211 , 212 ] (HBD is urea), ethaline [ 161 , 210 , 213 , 214 ] (HBD is ethylene glycol), glyceline [ 82 , 210 , 215 ] (HBD is glycerol), and propoline [ 216 , 217 ] (HBD is propylene glycol). Over the last five years, their structures and properties have been investigated intensively and the main interactions have been determined.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
“…Glyceline also exhibits over-saturation of HBD groups, which leads to higher cohesive forces within the bulk liquid and to a higher viscosity than ethaline due to more extensive interactions between HBDs. Another comparison of the choline-based DESs was performed by Ferreira et al [ 216 , 217 ]. In their first work [ 216 ], they developed a non-polarizable OPLS-based FF for propeline.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…114,127,128 Refinement of FF parameters have meant that subsequent classical simulations have continued to improve in the prediction and reproduction of DES physical properties, including density, surface tension, heat capacity, and viscosity. 105,108,113,[129][130][131][132][133][134] Solvent organization can also be easily derived from bulk-phase MD simulations. For example, computed center-of-mass radial distribution functions (RDFs) by Sun et al revealed that the long-range ordering of intercalating cations and anions in neat ChCl diminished with increasing concentration of urea molecules in CCU.…”
Section: Solvent Organizationmentioning
confidence: 99%
“…The earliest reported MD simulations of DESs came a decade after their initial discovery 114,127,128 . Refinement of FF parameters have meant that subsequent classical simulations have continued to improve in the prediction and reproduction of DES physical properties, including density, surface tension, heat capacity, and viscosity 105,108,113,129–134 . Solvent organization can also be easily derived from bulk‐phase MD simulations.…”
Section: Molecular Dynamicsmentioning
confidence: 99%